UMPSA empowers advanced TVET and international mobility - Mimi Rabita, Abd Wahit (UMPSA, 2024)
KUALA LUMPUR, 20 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) which is a university in the Malaysian Technical Universities Network (MTUN) has implemented various initiatives to strengthen the Technical and Vocational Education and Training Agenda (TVET).